Nghiên cứu ảnh hưởng của nanosilica đến tính chất cơ học của màng polyme epoxy DER 671X75. - Huy Cường, Huỳnh Lê; Diệu, Trần Vĩnh; Thành, Nguyễn Đắc; Yến Oanh, Đoàn Thị (Vietnam Journal of Chemistry, 2017)
Study on the effects of silica nanoparticles (nanosilica) and modified nanosilica to mechanical properties of polymer coating film based on epoxy resin DER 671X75. Surface modification of nanosilica by 3-aminopropyltriethoxy silan (APTES) was characterized by Fourier Transform Infrared Spectrometry (FTIR), Scanning Electron Microscopy (SEM) and Thermo Gravimetric Analysis (TGA). Dispersions of nanosilica and modified nanosilica in epoxy resin DER 671X75 were carried out by stirring and ultrasonic vibration. The structures of the materials were characterized by SEM. The mechanical temperature properties were chacrcterized by TGA. The results show that nanosilica and modified nanosilica are good dispersed and improved mechanical properties of polymer coating film based on epoxy resin DER 671X75. Keywords. Silica nanoparticles, nanosilica, modified nanosilica, 3-aminopropyltriethoxy silan, epoxy resin DER 671X75.